Dirty beasts - Dahl, Roald; Blake, Quentin (Puffin Books London, 2016)
Roald Dahl has created a ghastly assortment of wicked beasts getting up to some extraordinary and unmentionable things in this comic collection of verse. Meet the clever pig with a plan to save his bacon, the scorpion who likes to sting, the giant toad who can jump from England to France, and lots more